Open visitation in adult icu: utopia or reality? - Cláudia Severgnini Eugênio; Emiliane Nogueira de Souza (Universidade Federal de Santa Maria, 2017)
Aim: to reflect about the implementation of open visitation policies in an Adult Intensive Care Unit (ICU). Method: a theoretical-reflective study based on the literature review, divided into three categories: the characterization of the open visitation in Brazil and in world; The perception of the patient, team and family; The influence of open visitation on clinical outcomes. Results: the implementation of the open visitation is a reality, established in some services in Brazil and in the world, which needs support from the professionals involved in the care process. The insertion of the family members in the ICUs can minimize the discomforts experienced by the families and patients during the hospitalization, once associated with the effective reception and communication of the care team. Final considerations: patients in ICU experience stress and anxiety. Thus, the inclusion of the family should be considered in one's therapeutic plan through open visitation.